Chemotherapy side-effect management using mobile phones. - Larsen, M; Rowntree, J; Young, A; Pearson, S; Smith, J; Gibson, O; Weaver, A; Tarassenko, L (2008)
Colorectal cancer is a major health problem in developed countries, accounting for a significant proportion of deaths in the population. Advances in chemotherapy treatment have led to therapy being delivered in the home-setting, which presents challenges in ensuring that treatment-related side-effects are detected and reported to clinical staff in an appropriate time-frame. A telemedicine system has been developed using a mobile-phone platform to allow patients to complete symptom diaries which trigger alerts paged to their nurse in the event of severe side-effects. Six patients used this system for two cycles of oral chemotherapy. Two cases of moderate symptoms deteriorating to more severe conditions were observed, and individual self-care and treatment advice were presented to these patients.